2018
DOI: 10.1108/hff-03-2017-0112
|View full text |Cite
|
Sign up to set email alerts
|

Study of inception point, void fraction and pressure over pooled stepped spillways using Flow-3D

Abstract: Purpose -While many stepped spillways geometry design guidelines were developed for flat steps, designing pooled steps might be an appropriate alternative to spillways working more efficiency. This paper aims to deal with the inception point of air-entrainment and void fraction in the different height of the pools. Following that, pressure distribution was evaluated in aerated and non-aerated regions under the effect of different heights of the pools and slopes through the use of the FLOW-3D software. Comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…With the development of computer science, numerical simulations based on Computational Fluid Dynamics (CFD) codes (e.g., Flow-3D(Three-Dimensional), Fluent) have been wildly used. The simulation results have been proved to be consistent with experimental results [21][22][23][24][25][26][27][28][29][30]. For tandem piers, Palau-Salvador et al [31] conducted numerical simulations around two submerged tandem piers and presented flow streamlines at different planes.…”
supporting
confidence: 66%
“…With the development of computer science, numerical simulations based on Computational Fluid Dynamics (CFD) codes (e.g., Flow-3D(Three-Dimensional), Fluent) have been wildly used. The simulation results have been proved to be consistent with experimental results [21][22][23][24][25][26][27][28][29][30]. For tandem piers, Palau-Salvador et al [31] conducted numerical simulations around two submerged tandem piers and presented flow streamlines at different planes.…”
supporting
confidence: 66%
“…A comparison of the results reported by Morovati and Eghbalzadeh [31] with Li and Yang [32] indicated that pressure distribution on flat and inclined steps followed a virtually S-shaped distribution. Inception point location was also researched by Munta et al [33], Bombardelli et al [34], and Morovati and Eghbalzadeh [35]. Morovati et al [3] investigated the effects of various configurations of openings on pooled stepped chutes, and they concluded that a staggered configuration of openings improved the chute's efficiency concerning the residual head.…”
Section: Introductionmentioning
confidence: 95%
“…Bombardelli et al [39] compared measured time-averaged velocities for the flows in stepped spillway using k − ε, RNG k − ε turbulent models and found that the results did not significantly vary between the turbulent models. Morovati and Eghbalzadeh [40], Bayon et al [41] and Valero et al [42] used RNG k − ε model and it was found to be better than other models. Abdulla [43] evaluated the performance of different turbulent models (k − ε, RNG k − ε and SST) using ANSYS-CFX for Froude number varying from 1.2 to 2.0 for flows around bridge piers where flow separation was significant.…”
Section: Introductionmentioning
confidence: 99%